Assessment of climate change impacts and issues to support the making of new Nông Thôn Mới (Vietnam’s National Target Program on New Rural Development) criteria for the 2021-2030 Strategy - Bui, Le Vinh; Imbach, Pablo; Talsma, Tiffany; Tran, Hong Thanh; Tran, Cong Thang; Nguyen, Ngoc Luan (2020)
This report showcases the results of the assessment conducted by the Vietnam National University of Agriculture, International Center for Tropical Agriculture, and the Institute of Policy and Strategy for Agriculture and Rural Development. The assessment aims to create new sets of criteria for the Nông Thôn Mới (NTM) program of Vietnam by investigating the impacts and issues brought by climate change. This is a part of the task, “Investigation and improvement of the national NTM criteria for rural development at all levels (commune, district, province) according to titles (standard, advanced, demonstration) in the period of 2021-2025.”